1976
DOI: 10.1090/s0002-9939-1976-0419525-4
|View full text |Cite
|
Sign up to set email alerts
|

Projective modules

Abstract: Abstract.In this note we prove that if R is a ring satisfying a polynomial identity and P is a projective left .R-module such that P is finitely generated modulo the Jacobson radical, then P is finitely generated. As a corollary we get that if R is a ring still satisfying a polynomial identity and M is a finitely generated flat /R-module such that M/JM is ^//-projective, then M is Rprojective, J denotes the Jacobson radical. 0. Introduction. In this note R denotes an associative ring with an identity element, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Here we have only partial results, based on the following Fact 5.4 [8,Lemma 2.4]. Let P be a projective right module over an arbitrary ring R. If P /P Jac(R) is finitely generated and so is P /P I for every prime ideal I , then P is finitely generated.…”
Section: Corollary 53 Let I Be An Ideal Contained In the Prime Radimentioning
confidence: 99%
“…Here we have only partial results, based on the following Fact 5.4 [8,Lemma 2.4]. Let P be a projective right module over an arbitrary ring R. If P /P Jac(R) is finitely generated and so is P /P I for every prime ideal I , then P is finitely generated.…”
Section: Corollary 53 Let I Be An Ideal Contained In the Prime Radimentioning
confidence: 99%
“…(b) In [14,Theorem 2.5], it is shown that any ring with polynomial identity is an L-ring. (c) [25,Corollary 3.3] shows that if a ring R has either left or right Krull dimension, then R is an L-ring.…”
Section: Example 41mentioning
confidence: 99%
“…As we have mentioned in the introduction, rings for which every supplement submodule of a finitely generated projective module is a direct summand have been widely studied (see [4,[6][7][8][11][12][13]16]). The aim of this section is to extend some of the characterizations of these rings to those in which every supplement submodule of a (non-necessarily finitely generated) projective module is a direct summand.…”
Section: Supplements As Summands Examplesmentioning
confidence: 99%
“…It is known that rings with polynomial identity, semihereditary rings and rings whose prime quotients rings are left Goldie rings verify the condition (i) of Corollary 3.4 for finitely generated projective modules (see [7,11] for more examples). Moreover, left noetherian rings and commutative domains verify the conditions of Corollary 3.4.…”
Section: Proof Follows From Corollary 32mentioning
confidence: 99%
See 1 more Smart Citation